Fundamentals of computers and data processing with basic - Price, Wilson T. (New York : Holt, Rinehart and Winston, 1983)
The book explains a better balance between the general descriptive material and programming using Basic.
Includes index.
ii 15/01/2019
Loans
Keywords: BASIC (Computer program language); Computer programming; Business